2006
DOI: 10.1002/pola.21776
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of the shrinkage of thermosets by the cationic curing of mixtures of diglycidyl ether of bisphenol A and 6,6‐dimethyl‐(4,8‐dioxaspiro[2.5]octane‐5,7‐dione)

Abstract: Ytterbium and lanthanum triflates were used as initiators to cure mixtures of diglycidyl ether of bisphenol A and 6,6‐dimethyl‐(4,8‐dioxaspiro[2.5]octane‐5,7‐dione) in several proportions. The evolution of the epoxy and 6,6‐dimethyl‐(4,8‐dioxaspiro[2.5]octane‐5,7‐dione) bands during curing and the linear ester groups in the final materials were evaluated with Fourier transform infrared in the attenuated‐total‐reflection mode. The use of a conventional cationic initiator, boron trifluoride monoethylamine, was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 18 publications
1
23
0
2
Order By: Relevance
“…In a previous work, 8 we studied the curing of mixtures of DGEBA epoxy resin with a cyclopropylic spiranic MA derivative (MCP), using lanthanide triflates as initiators. We observed that the higher the proportion was of MCP in the curing mixture, the lower the global shrinkage was.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In a previous work, 8 we studied the curing of mixtures of DGEBA epoxy resin with a cyclopropylic spiranic MA derivative (MCP), using lanthanide triflates as initiators. We observed that the higher the proportion was of MCP in the curing mixture, the lower the global shrinkage was.…”
Section: Resultsmentioning
confidence: 99%
“…4 The expandable character of MCP was proved and attributed to the change in the dipolar moment by the opening of the lactone ring. 8 Moreover, the amount of shrinkage is related to the size of the ring being opened; in general, the larger the ring is, the smaller the shrinkage is. 20 Therefore, six-membered lactones should produce a larger expansion on polymerizing than five-membered lactones.…”
Section: Shrinkagementioning
confidence: 99%
See 1 more Smart Citation
“…The enthalpies (J/g) for g-BL-containing mixtures are higher than SOE-containing samples. The enthalpies per epoxy equivalent are higher for the samples with lactone, and close to enthalpy of pure DGEBA [30,31]. This indicates that the enthalpy is mainly related to the ring opening of oxirane groups.…”
Section: Dopo-bq-glymentioning
confidence: 90%
“…The improved thermal stability of the photocured materials can be related to their higher degree of cross-linking and to the fact that lanthanide triflates can catalyze the decomposition reactions at high temperatures. [32,33] As in thermally cured samples, it is observed that the presence of PhBL increases the thermal degradability due to the introduction of ester linkages in the network via intermediate SOE formation and polymerization. The degradative process of UV-cured samples takes place in a narrow range of temperatures because volatilization of the decomposition fragments is fast at such high temperatures.…”
Section: Photocuringmentioning
confidence: 97%